Ethylene Inhibitors Enhance Shoot Organogenesis of Gloxinia (Sinningia speciosa). (17th October 2012) - Chae, Soo Cheon; Kim, Haeng Hoon; Park, Sang Un
Abstract : Shoot organogenesis and plant regeneration in Sinningia speciosa were improved using ethylene inhibitors. The leaf explants were cultured on initial shoot regeneration media (MS media with BAP at 2 mg/L + NAA at 0.1 mg/L) supplemented with different concentrations of aminoethoxyvinylglycine (AVG), cobalt chloride (CoCl2 ), and silver thiosulphate (STS). The addition of AVG, CoCl2, and STS significantly improved the regeneration frequency giving higher shoots per explant and longer shoot length. The highest shoot growth was found when STS at 5 mg/L was incorporated with generation medium, performing highest regeneration frequency with highest number of shoots. This treatment (STS at 5 mg/L) produced 40% more shoots per explant compared to control followed by STS at 10 mg/L with increasing 37% more shoots compared to control. In the cases of AVG and CoCl2 the highest shoot number per explant was found at 1 mg/L. Treated with AVG and CoCl2 at 1 mg/L increased shoot number by 16 and 12%, respectively, compared to control. Ethylene inhibitors could be used as a possible micropropagation and plant transformation protocol in S. speciosa for plant regenerations.